Discovery of selective, orally bioavailable inhibitor of mouse chitotriosidase. Issue 3 (1st February 2018) - Mazur, Marzena; Bartoszewicz, Agnieszka; Dymek, Barbara; Salamon, Magdalena; Andryianau, Gleb; Kowalski, Michał; Olejniczak, Sylwia; Matyszewski, Krzysztof; Pluta, Elżbieta; Borek, Bartłomiej; Stefaniak, Filip; Zagozdzon, Agnieszka; et al.
Graphical abstract: Abstract: This article describes our work towards the identification of a potent and selective inhibitor of mouse chitotriosidase (mCHIT1). A series of small molecule inhibitors of mCHIT1 and mAMCase have been developed from early lead compound1 . Examination of synthetized analogues led to discovery of several novel highly potent compounds. Among them compound9 (OAT-2068 ) displays a remarkable 143-fold mCHIT1 vs . mAMCase selectivity. To explain the observed SAR molecular docking experiments were performed, which were in line with the experimental data from the enzymatic assays. Inhibitor9 (OAT-2068 ) was found to have an excellent pharmacokinetic profile. This, together with high activity and selectivity, makes the compound an ideal and unique tool for studying the role of CHIT1 in biological models.